Inversores fotovoltaicos conectados à rede com armazenamento de energia – classificação, recomendações técnicas e gerenciamento - Bellinaso, Lucas Vizzotto (2017)
Grid-connected photovoltaic systems with energy storage have features of conventional gridconnected inverters and uninterruptible power supplies. In these systems, all elements, which include photovoltaic generator, batteries, loads and electric grid, are connected to the same equipment named multifunctional photovoltaic converter. As it is a recent technology, there are many research opportunities in this theme, from classifications and standards to specific problems. This study investigates this field in a comprehensive manner, proposing classifications, technical recommendations and a power management strategy. Initially, classifications are proposed considering system configuration and continuity of supply to the loads. In the following, technical recommendations related to grid and load compatibility, as well as safety technical recommendations, are proposed. The last proposal consists on a power management strategy which defines the operation mode of the static converters and system elements as a function of the energy scarcity. Experimental results of the power management are presented in order to validate the proposals. In this way, this thesis contributes to the development of multifunctional photovoltaic converters technology so that the distributed generation becomes more independent of solar availability and can better collaborate with the electric system.